Revitalizing Da'wah through YouTube: Toward a Digitally Literate Society - Sabil Mokodenseho; Novita Tabo; Nini Mokodonseho; Naneng Durand; Kurnia Mamonto; Yohana Akontalo (Westscience Press, 2024)
This qualitative study explores the role of YouTube in revitalizing Da'wah (Islamic propagation) and its implications for promoting digital literacy in Indonesia. Drawing on in-depth interviews with religious scholars, Da'wah practitioners, YouTube content creators, and active viewers, as well as content analysis of Da'wah videos on YouTube and participant observation of online Da'wah activities, the research investigates the strategies, reception, and impact of digital Da'wah efforts. The findings reveal that YouTube serves as a dynamic platform for religious communication, enabling practitioners to reach diverse audiences and convey religious messages in engaging formats. While YouTube-based Da'wah has the potential to promote digital literacy by providing access to diverse perspectives and fostering critical thinking skills, challenges such as misinformation and algorithmic bias underscore the need for media literacy education among viewers. Overall, this study contributes to understanding the intersection of digital media, religious communication, and digital literacy in Indonesia's diverse socio-cultural context.